SELEKSI FITUR DAN PREFERENSI PENYERANG TERBAIK LIGA INGGRIS BERBASIS FISHER’S DISCRIMINANT RATIO, K-MEANS CLUSTERING DAN TOPSIS - Alif Sefty Wiyantoro (JURNAL ILMIAH INFORMATIKA, 2019)
Football is a sport that is carried out by several people in a team, each player in a team has their respective roles in a match. One of the important positions in a team is as an attacker whose job is to score goals for the team. This research aims to determine the best attackers in the English Premier League from all teams competing in the 2018-2019 season based on data from the Fifa 19 game. There are several stages in this research, the first step is clustering with K-Means Clustering method, the second step is feature selection using Fisher Discriminant Ratio method (FDR) and then weighted and calculated using TOPSIS (The Technique for Order of Preference by Similarity to Ideal Solution) method. The calculation of the preference value for each player is based on the weight value of the features that have passed the selection stage. The player who has the highest preference value will be chosen as the best player